ANALISIS HARGA POKOK PESANAN BANNER PADA CV. ADI PUTRA UTAMA - Widiyana, Luthfia (P3M STIE Mulia Darma Pratama, 2024)
Sales play a crucial role for a company, as they ensure that the products produced can be sold, generating revenue for the company. To achieve this, a company must determine an appropriate selling price, as the price is a significant factor for the general public. The higher the price of a product, the more it may negatively impact sales. This research focuses on the analysis of job order costing. The objective of this study is to understand how the cost of producing banners is determined at CV. Adi Putra Utama. This research employs a quantitative method, with data analysis conducted using a descriptive approach. Data collection methods include observation, interviews, and documentation, utilizing both primary and secondary data sources. In determining the cost of production, CV. Adi Putra Utama currently calculates the cost without distinguishing between raw materials and auxiliary materials. As a result of the production cost analysis, the company's gross profit is found to be Rp. 8,361, which is lower than the gross profit of Rp. 10,701 that would be obtained using the job order costing method.